Comparative economic systems - Loucks, William N. (New York: Harper & Row, 1965)
The book deals with the following topics: Capitalism; The Marxian Theory of Socialism and Communism; Modern Socialism and Communism; British Socialism; The Economy of the Soviet Union; Communism in Yugoslavia and Communist China; and Economic Planning in India.
Includes bibliographies.
rpm 26/10/2017
Loans
Keywords: Comparative economics; Economic systems